The Effect of Work Motivation and Entrepreneurship Orientation on Business Performance through Entrepreneurial Commitments of Coffee Shops in Makassar - Muhammad Nadhar; Amiruddin Tawe; Dian Anggraece Parawansa (International Review of Management and Marketing, 2017)
This study aimed to explore the effect of work motivation and entrepreneurship orientation on businesses performance of Small and Medium Enterprises (SMEs), particularly for the coffee shop in Makassar. This study was included in the category of explanatory research that aimed to explore the facts through the collection of secondary and primary data with questionnaires and interview techniques related to entrepreneurial orientation, achievement motivation and its impact on business performance in the Small and Medium Enterprises (SMEs) in Makassar. This study also used Path Analysis approach as an engineering approach in statistics to examine direct and indirect relationships between exogenous and endogenous variables. Some important aspects need to be explored explicitly related to the method used. The important issues included the nature of the study, the type of investigation, the level of intervention research, the situation of the study, the unit of analysis, and the time horizon. The results of this study showed that the entrepreneurial orientation and motivation either partially or simultaneously to the coffee shop business in Makassar had a positive effect. In this case, entrepreneurial orientation had a positive and significant effect on business performance. Meanwhile, the orientation of work motivation, directly and indirectly, had a positive and significant effect on the business performance of coffee shop business in Makassar. In other cases, the commitments had important roles in giving positive effect to business performance related to the coffee shop business in Makassar.